PENCEGAHAN DEMAM BERDARAH PADA LINGKUNGAN SEKOLAH TAMBOSUPA MELALUI PERILAKU HIDUP BERSIH-SEHAT - Astrid Indalifiany; Sabarudin Sabarudin; Halik Halik; Nurull Hikmah; La Ode Nggawu; Fifi Nirmala (Universitas Halu Oleo, 2023)
Dengue fever is an infectious disease spread by the bite of the Aedes mosquito, especially Aedes aegypti. The fact that the Aedes aegypti mosquito often bites during the day during school activities, makes schools a potential location for the spread of DHF. To stop the spread of dengue fever, clean and healthy living behavior (PHBS) can be implemented by washing hands properly, keeping classrooms clean, eating healthy food, exercising regularly, and getting enough sleep. Other efforts are wearing a mask when in crowds, maintaining a safe distance, and using 3M-plus to prevent dengue, such as draining, covering, and burying. The purpose of this service is to educate junior high school students in Tambosupa Konawe Selatan Village about maintaining a clean school environment and avoiding various diseases, especially DHF, to increase their knowledge and skills regarding clean and healthy behavior (PHBS).